2018
DOI: 10.18203/2349-2902.isj20181587
|View full text |Cite
|
Sign up to set email alerts
|

Varicose vein surgery stripping method compared to radio frequency ablation

Abstract: Background: This randomised study was conducted to evaluate clinical, patient based outcomes after RFA and conventional surgery in a selected population. Methods: This study was conducted in the Meenakshi Medical College Hospital and Research Institute, Enathur, Kanchipuram, Tamil Nadu, India. Results: In present study, it was reported that 150 patients in total were assessed in the study, out of which, 110 were randomised, 100 underwent the intervention as a daily procedure. 50 patients underwent RFA and 50 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…Pseudothrombophlebitis was also seen more in the conventional method (26.7%) than saphenous vein space packing technique (10%). In the study findings of our study were found to be similar to the findings of by Figueiredo et al and Potula et al 8,12 Our main objective was to study the effect of packing on post-operative pain as pain in the most undesirable experience a patient may have immediately postprocedure. The pain was assed using VAS scale on postoperative day 2, day 4, day 7 and day 30 post-operative day.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Pseudothrombophlebitis was also seen more in the conventional method (26.7%) than saphenous vein space packing technique (10%). In the study findings of our study were found to be similar to the findings of by Figueiredo et al and Potula et al 8,12 Our main objective was to study the effect of packing on post-operative pain as pain in the most undesirable experience a patient may have immediately postprocedure. The pain was assed using VAS scale on postoperative day 2, day 4, day 7 and day 30 post-operative day.…”
Section: Discussionsupporting
confidence: 89%
“…In our study which is similar to the study done by Potula who showed an average operating time of 52 mins. 8 In our study the side of limb affected was almost equal with 31 (51.6%) on left side and 29 (48.4%) on right side in comparison to a study performed by Dur, Mackaay et al where the Right limb was involved in 48.55% and left limb in 51.45% of the subjects under study. 9 The most common presenting symptoms were dilated veins seen in about 90% of the subjects which was comparable to a study findings of Campbell et al Pain as a symptom was seen in only 23% of the subjects in our study as compared 23% in the study performed by W. B Campbell et al The most common complications seen among the study subjects was prominent veins 54 (90%) followed by pigmentation 30 (50%).…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation